A non-fatal intoxication and seven deaths involving the dissociative drug 3-MeO-PCP. (June 2017) - Johansson, Anna; Lindstedt, Daniel; Roman, Markus; Thelander, Gunilla; Nielsen, Elisabet I.; Lennborn, Ulrica; Sandler, Håkan; Rubertsson, Sten; Ahlner, Johan; Kronstrand, Robert; Kugelberg, Fredrik C.
Highlights: A validated LC–MS/MS method for quantitative analysis of 3-MeO-PCP is described. 3-MeO-PCP continues to be abused in Sweden despite being scheduled. Symptoms include tachypnea, tachycardia, hypertension, fever and lactic acidosis. 3-MeO-PCP half-life was approximately 11 h and confirmed previous data. In a fatal mono-intoxication the blood concentration of 3-MeO-PCP was 0.38 μg/g. Abstract: Introduction: 3-methoxyphencyclidine (3-MeO-PCP) appeared on the illicit drug market in 2011 and is an analogue of phencyclidine, which exhibits anesthetic, analgesic and hallucinogenic properties. In this paper, we report data from a non-fatal intoxication and seven deaths involving 3-MeO-PCP in Sweden during the period March 2014 until June 2016. Case descriptions: The non-fatal intoxication case, a 19-year-old male with drug problems and a medical history of depression, was found awake but tachycardic, hypertensive, tachypnoeic and catatonic at home. After being hospitalized, his condition worsened as he developed a fever and lactic acidosis concomitant with psychomotor agitation and hallucinations. After 22 h of intensive care, the patient had made a complete recovery. During his hospitalization, a total of four blood samples were collected at different time points. The seven autopsy cases, six males and one female, were all in their twenties to thirties with psychiatric problems and/or an ongoing drug abuse. Methods: 3-MeO-PCP was identified with liquid chromatography (LC)/time-of-flight technology and quantified using LC-tandem mass spectrometry. Results: In the clinical case, the concentration of 3-MeO-PCP was 0.14 μg/g at admission, 0.08 μg/g 2.5 h after admission, 0.06 μg/g 5 h after admission and 0.04 μg/g 17 h after admission. The half-life of 3-MeO-PCP was estimated to 11 h. In the autopsy cases, femoral blood concentrations ranged from 0.05 μg/g to 0.38 μg/g. 3-MeO-PCP was the sole finding in the case with the highest concentration and the cause of death was established as intoxication with 3-MeO-PCP. In the remaining six autopsy cases, other medications and drugs of abuse were present as well. Conclusion: Despite being scheduled in January 2015, 3-MeO-PCP continues to be abused in Sweden. Exposure to 3-MeO-PCP may cause severe adverse events and even death, especially if the user does not receive life-supporting treatment.